Can Banking Union foster market integration, and what lessons does that hold for capital markets union? - Ignazio Angeloni; Rainer Haselmann; Florian Heider; Loriana Pelizzon; Jonas Schlegel; Tobias Tröger (Leibniz Institute for Financial Research SAFE, 2024)
Over the past decade, the Single Supervisory Mechanism focused on making banks safer, resulting in stronger banks but limited euro area cross-border integration. We argue that overbanking hinders both cross-border integration for the EU and the development and integration of capital markets. In addition to a common supervisory authority and to attain the strong and integrated financial system Europe needs going forward, the Banking Union and Capital Markets Union need to coexist and complement each other. This document was provided/prepared by the Economic Governance and EMU Scrutiny Unit at the request of the ECON Committee.
Keywords: 330; Banking Union; Capital Markets Union; Market Integration; Overbanking